Inter-particle structural fluctuation of Prussian blue analogue as investigated by X-ray microbeam diffraction. (4th February 2021) - Nagai, Ichiro; Yasuda, Nobuhiro; Moritomo, Yutaka
Abstract: The X-ray microbeam diffraction from each particle leads to a deeper structural characterization, i.e. inter-particle structural fluctuation, of powdery compound. Here, we performed X-ray microbeam diffractions of Na x Co1− z Ni z [Fe(CN)6 ] y at BL40XU beamline of SPring-8. In the whole region of z, the inter-particle structural fluctuation is negligible in the as-grown powder. We found that the average ( d 012 ̄ ) of the spacing ( d 012 ) of the (012) plane decreases with X-ray irradiation time ( t ). The standard deviation ( σ ) of d 012 steeply increases with t from 0.006 Å at t = 1 s to 0.031 Å at t = 60 s, indicating that inter-particle structural fluctuation is induced by the X-ray irradiation.